Impact of corporate culture on plant maintenance in the Nigerian electric-power industry - Eti, Mark C.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2006)
Comparisons have been made of modern maintenance-practices, i.e. in the more developed economies, with what occurs in Nigeria. Significant differences arise due to variations in corporate culture, pertinent learning opportunities and effectiveness of strategic planning. The managerial implications of these divergences are discussed. A systematic, total productive-maintenance (TPM) approach needs to be adopted to allow corporate changes to be implemented at a rate commensurate with each organization's evolving culture. This paper advocates that maintenance should be managed better, in each organization, so as to cultivate a sense of ownership in the operators. Also autonomous maintenance-teams, consisting of operators, engineers and managers, should be set up with the aims of improving personnel competence and equipment performance.